Death of God or collapse of the idols? Approximation to the theological thought of Jean-Luc Marion - Porcel Moreno, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
Based on Nietzsche’s thinking, Jean-Luc Marion affirms the «death of God» along with him. However, the French philosopher provides a new reinterpretation of the «death of God» proclaimed by Nietzsche. For Marion, the one proclaimed dead is not the God alive in the historic-positive religions, but a conceptual idol who has been gestating all throughout the history of metaphysics. The intent of this article is to merely show how Marion presents a more original idea of the divine, an idea that doesn’t turn the divine into the visible and which doesn’t stop at the first visible or concept, but one that shows its invisibility from the distance that opens from the man.